Efektivitas Metode Tahfidz Al-Qur’an dalam Pembelajaran Anak di Masjid Nabawi Madinah - Khairil Mursyid, Fathoni; Pasaribu, Munawir (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study examines in depth the Qur'an memorization method applied to children at the Prophet's Mosque, one of the world's leading centers for Qur'an learning. The focus of the study is to analyze the approach used to facilitate the process of memorizing the Qur'an for young children, as well as the factors supporting its success. The main problem raised is how the tahfidz method at the Prophet's Mosque can maximize the memorization potential of children while maintaining the quality of reading and understanding. The research method uses a qualitative approach with data collection techniques through observation, interviews, and documentation studies. The results show that the tahfidz method at the Prophet's Mosque integrates three main components: (1) a classical system with group division based on ability, (2) a structured repetition technique (tikrar), and (3) individual mentoring by teachers who have passed special certification. In addition, the spiritual environment of the Prophet's Mosque and community support are key factors that strengthen children's motivation. Evaluation is carried out periodically through weekly and monthly memorization tests (simaan). The conclusion of this study confirms that the success of the tahfidz method at the Prophet's Mosque lies not only in memorization techniques, but also in creating a holistic learning ecosystem that integrates cognitive, spiritual, and social aspects. These findings can serve as a reference for other tahfidz institutions in developing effective learning systems.